2001
DOI: 10.1159/000050628
|View full text |Cite
|
Sign up to set email alerts
|

Tumor M2 Pyruvate Kinase in Plasma of Patients with Urological Tumors

Abstract: The M2 isoenzyme of pyruvate kinase (M2-PK) is specifically expressed in tumor cells (TU M2-PK) and may therefore provide a tumor marker for malignancies. We have investigated the plasma concentrations of TU M2-PK in patients with renal cell carcinoma (RCC), transitional cell carcinoma of the bladder (BCA), prostate cancer (PCA) and benign prostatic hyperplasia (BPH). TU M2-PK was quantified with a commercially available enzyme-linked immunosorbent assay (ELISA) kit. Using this ELISA kit, plasma samples of 57 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 3 publications
1
22
0
1
Order By: Relevance
“…Additionally, we also found no correlation to PSA levels, TNM system and Gleason Score. Similar results were obtained in a separate study [15]. In TCC we found no higher levels of TuM2-PK in comparison to the control group.…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, we also found no correlation to PSA levels, TNM system and Gleason Score. Similar results were obtained in a separate study [15]. In TCC we found no higher levels of TuM2-PK in comparison to the control group.…”
Section: Discussionsupporting
confidence: 91%
“…Christofk et al observed that stable knockdown of pyruvate kinase M2 isoform (PKM2) in the human lung cancer cell line H1299 resulted in decreased rates of glucose metabolism and reduced cell proliferation (17). These results were echoed in clinical studies reported by Roigas et al, who observed that PKM2 levels in patients with malignant renal tumors were significantly higher than in healthy donors (114). In addition, PKM2 has been shown to be capable of predicting disease recurrence in renal cell carcinoma patients after nephrectomy (95).…”
Section: Sod and Cell Metabolism In Cancer Preventionmentioning
confidence: 82%
“…In lung cancer, a metaanalysis revealed that M2-PK can be a potential biomarker for diagnosis of non-small cell lung cancer with pooled sensitivity, specificity, positive likelihood ratio (PLR), negative likelihood ratio (NLR) of 0.69 (0.65-0.72), 0.92 (0.89-0.94), 7.84 (5.92-10.38), and 0.36 (0.32-0.40) [37]. In addition to the previous non-metastatic cancers, plasma M2-PK concentrations might be a potential biomarker of advanced renal cell cancer with a sensitivity of 66.7% and specificity of 95% [40].…”
Section: Discussionmentioning
confidence: 99%
“…The mean sensitivity and specificity (0.76 and 0.80) of M2-PK were even higher than those of ERCP (0.74 and 0.70) [54], the current benchmark of BTC pretreatment diagnosis [4]. Though the LR showed imperfect robustness as a lonely marker [39][40][41][51][52][53], this easy available M2-PK test is highly recommended alongside conventional cytological and histological examinations for BTC by Navaneethan et al They found that a combination of markers -elevated M2-PK (>109.1 U/l) or CA 19-9 (>33 U/ml) or positive biliary brushing increased the sensitivity (88.2%) and the specificity (88.2%) in diagnosing malignant biliary strictures, with an AUC of 0.89 [25]. In another study, combined M2-PK with CA19-9 did not improve the diagnostic sensitivity and specificity over the M2-PK alone [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation